2018
DOI: 10.1007/s11547-018-0928-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low-kVp scan technique on oral contrast density at abdominopelvic CT

Abstract: Oral contrast density is strongly influenced by kVp, supporting use of more dilute oral contrast when using lower-kVp techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Recently, in a phantom setup, Patino et al (17) confirmed 28%-200% higher attenuation on low-kVp/low-keV images obtained with OCM solutions of different concentrations, and Sheafor et al (18) reproduced these results on low-kVp images. These investigators suggested the use of OCM solutions of 6 mg I/mL to maintain the desirable attenuation values achieved using a standard OCM concentration at 120 kVp (18). Our clinical trial confirms the outcome of the published phantom experiments, and, despite a 25% reduction in ICM concentration, higher bowel attenuation was achieved with 100 kVp and 50-65 keV images compared with BCM/120 kVp images, with preference.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Recently, in a phantom setup, Patino et al (17) confirmed 28%-200% higher attenuation on low-kVp/low-keV images obtained with OCM solutions of different concentrations, and Sheafor et al (18) reproduced these results on low-kVp images. These investigators suggested the use of OCM solutions of 6 mg I/mL to maintain the desirable attenuation values achieved using a standard OCM concentration at 120 kVp (18). Our clinical trial confirms the outcome of the published phantom experiments, and, despite a 25% reduction in ICM concentration, higher bowel attenuation was achieved with 100 kVp and 50-65 keV images compared with BCM/120 kVp images, with preference.…”
Section: Discussionmentioning
confidence: 87%
“…The attenuation of diluted water-soluble OCMs like iohexol increases during enteral transit as water is absorbed from the intestine, rendering higher CT attenuation distally (13,18). Compared with the standard dose, rICM exhibited a lesser difference in attenuation between distal and proximal segments compared with sICM at 100 kVp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advent of new CT scanners and imaging protocols, including a low-peak-kilovoltage technique with an iterative reconstruction algorithm and monochromatic low kiloelectron volts as in dual-energy/spectral CT imaging, the dose of the oral contrast medium can potentially be reduced (3,4). This is exactly the same as for intravenously injected iodinated contrast media: When tube voltage is reduced, the attenuation of iodine is increased by two-to fourfold, and thus the contrast medium dose can be consequently reduced (5).…”
mentioning
confidence: 99%